Case report: Hypoparathyroidism-sensorineural hearing loss-renal dysplasia without febrile seizures: a novel mutation in the GATA3 gene - Chen, Haibin; Zhang, Yudi; Yang, Xueyao; Li, Yongzhen (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to summarize the diagnostic and treatment experience of a case of Hypoparathyroidism-Sensorineural Hearing Loss-Renal Dysplasia (HDR) syndrome caused by a heterozygous mutation in the GATA3 gene.MethodsThe diagnostic and treatment process of the patient with HDR syndrome in our hospital was compared and analyzed.ResultsA 9-month-old male infant with a history of poor physical condition and increased susceptibility to infections. At the age of 2 months, ptosis was observed in the left eye. Laboratory tests revealed decreased serum calcium, elevated blood phosphorus levels, and reduced parathyroid hormone (PTH) levels, indicating the presence of “Hypoparathyroidism”. Genetic testing identified a heterozygous mutation in the GATA3 gene in the patient, specifically a nucleotide change from G to T at position 800 (c.800G>T). This mutation resulted in the substitution of cysteine with phenylalanine at amino acid position 267 (p.C267F). The missense mutation was determined to be both pathogenic and novel.ConclusionEarly genetic testing should be prioritized, and regular monitoring of kidney development and hearing status is essential. The reported case, featuring the novel GATA3 gene mutation c.800G>T (p.C267F), contributes to the enrichment of the genetic database.